Simvastatin Reduces Neutrophils Infiltration Into Brain Parenchyma After Intracerebral Hemorrhage via Regulating Peripheral Neutrophils Apoptosis - Zhang, Jianbo; Shi, Xia; Hao, Na; Chen, Zhi; Wei, Linjie; Tan, Liang; Chen, Yujie; Feng, Hua; Chen, Qianwei; Zhu, Gang (Frontiers in Neuroscience, 2018)
Statins, known for their lipid-lowering effects, also have immunomodulatory properties. This study aims to examine whether systematic simvastatin administration could decrease polymorphonuclear neutrophils (PMNs) infiltration into brain tissue, as well as alleviate neuroinflammation in a rat model of intracerebral hemorrhage (ICH). The ICH model was induced in adult male Sprague–Dawley rats by an injection of autologous blood. Animals randomly received simvastatin (i.p. 2 mg/kg) or vehicle daily from 5 days before ICH until sacrificed. Routine blood counts, brain water content, neurological scoring, immunofluorescence and RT-PCR were conducted to evaluate the anti-inflammatory effect of simvastatin following ICH. Furthermore, flow cytometric and western blotting analysis were implemented for elucidating the mechanisms involved in simvastatin-induced reduction of neutrophil brain-invading. Elevated PMNs count and neutrophil-to-lymphocyte ratio in circulation were detected in rat model of ICH, which was reversed by using simvastatin. Simvastatin effectively alleviated PMNs infiltration and proinflammatory factors release in perihematomal area, as well as attenuated ICH-induced brain edema and neurological deficits. Simvastatin significantly downregulated the expression of antiapoptotic protein-Mcl-1 while increased the level of proapoptotic protein-Bax and cleaved caspase 3 in PMNs. Simvastatin treatment significantly alleviated PMNs brain-infiltrating and subsequent neuroinflammatory reaction after ICH, in part by accelerating peripheral PMNs apoptosis through disorganized the expression of apoptotic related proteins. Our data provided new evidence for simvastatin application on patients with ICH.